The Effect of Taxpayer Awareness on Intention to Pay Taxes - Dewi Kusuma Wardani; Ayu Indra Wati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to examine the Analysis of Taxpayer Awareness, Tax to Pay Taxes. This study uses a quantitative description method and primary data using a questionnaire. The number of samples in this study were 100 student respondents at the Universitas Sarjanawiyata Tamansiswa Yogyakarta. Sampling in this study using a convenience sampling technique. This study provides results that taxpayer awareness affects the intention to pay taxes.